A Review on Performance Calculation and Design Methodologies for Horizontal-Axis Wind Turbine Blades - Rongyu Zha; Siyuan Wu; Chang Cai; Xiaohui Liu; Dian Wang; Chaoyi Peng; Xuebin Feng; Qiuhua Chen; Xiaohui Zhong; Qing’an Li (Energies)
The efficient, low-cost, and large-scale development and utilization of offshore wind energy resources is an inevitable trend for future growth. With the continuous increase in the scale of wind turbines and their expansion into deep-sea locations, there is an urgent need to develop ultra-long, flexible blades suitable for future high-capacity turbines. Existing reviews in the field of blade design lack a simultaneous focus on the two core elements of blade performance calculation and design methods, as well as a detailed evaluation of specific methods. Therefore, this paper reviews the performance calculation and design methodologies of horizontal-axis wind turbine blades from three aspects: aerodynamic design, structural design, and coupled aero-structural design. A critical introduction to various methods is provided, along with a key viewpoint centered around design philosophy: there is no global optimal solution; instead, the most suitable solution is chosen from the Pareto set according to the design philosophy. This review not only provides a concise and clear overview for researchers new to the field of blade design to quickly acquire key background knowledge but also offers valuable insights for experienced researchers through critical evaluations of various methods and the presentation of core viewpoints. The paper also includes a refined review of extended areas such as aerodynamic add-ons and fatigue characteristics, which broadens the scope of the review to touch on multiple research areas and inspire further research. In future research, it is crucial to identify new key issues and challenges associated with increased blade length and flexibility, address the challenges faced in integrated aero-structural design, and develop platforms and tools that support multi-objective optimization design of blades, ensuring the safe, stable, and orderly development of wind turbines.